Problematika Aplikasi Zoom dalam Pembelajaran Fiqih di IAIN Sorong - Hermanto Hermanto; Fardan Abdillah M. (LPPM IAIN Sorong, 2022)
ABSTRACT Title : Zoom Aplication Problems in Fiqih Learning in English Class of IAIN Sorong The purpose of this study was to investigate student perceptions of Fiqh learning using the Zoom application and to explore the difficulties faced by students in learning Fiqh using the Zoom application. The type of research used in this research is qualitative research. Qualitative research focuses on natural phenomena or events. The research subjects were English students of IAIN Sorong Papua Barat who studied Fiqh courses. The research procedure carried out in this study was to collect data in the form of questionnaires, interviews, and documentation. In this study, the data analysis used consisted of 3 stages, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that students' perceptions of the use of the Zoom application in Fiqh learning include: active participation in learning, ease of understanding the material, effectiveness of using the Zoom application, benefits of using the Zoom application, new experiences in knowledge, efficiency in establishing communication, creativity in learning, and motivation study. The main difficulty for students in using the Zoom application is an unstable internet network. The solution to overcome these difficulties is to find a place that has a more stable network, or the learning is shifted to Whatsapp Groups. Key Word: Problematics, Zoom Application, Fiqh Learning